DETERMINANTS OF SELF-EFFICACY AND ITS IMPLICATIONS FOR JOB SATISFACTION OF GENERATION Z (STUDY ON GENERATION Z IN THE SOUTH TANGERANG REGION): DETERMINANTS OF SELF-EFFICACY AND ITS IMPLICATIONS FOR JOB SATISFACTION OF GENERATION Z (STUDY ON GENERATION Z IN THE SOUTH TANGERANG REGION) - Kusumawati, Yasmin; Husainah, Nazifah (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This study was conducted with the aim of finding out and analyzing the influence of